(untitled) (The Review of Diabetic Studies, 2025)
Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders that are mostly caused by a deficiency in the enzymes that are necessary for the manufacture of cortisol. Typically, classical studies focus on specific gene changes. The utilisation of a systems-level approach that incorporates a computational approach provides a unique framework for understanding the complicated mechanism of CAH-associated core gene disease. As a result of this procedure, the POMC, CYP21A2, CYP17A1, CYP11B1, CYP11B2, and HSD3B2 core genes have been identified via a computational approach. These screened core genes, POMC, CYP21A2, CYP17A1, CYP11B1, CYP11B2, and HSD3B2, make it possible to illustrate how CAH progression occurs. It can have a negative impact on the entire steroidogenic network. These changes can then result in hormonal imbalances, adrenal hyperplasia, and other symptoms that can be observed in clinical settings. The mapping of protein-protein interactions, regulatory pathways, and downstream metabolic effects explains how this occurs. Furthermore, this approach enables the discovery of new genes that are linked to therapies that are being administered at currently available hormonal therapies. This article provides a summary of how the computational approach is used to focus on the way in which the core genes CYP11B1, CYP11B2, CYP21A2, CYP17A1, POMC, and HSD3B2 work together in the progression of CAH. The study also could contribute to the development of targeted therapies that are more effective in the treatment of this complicated CAH disease.